Allelic sequence diversity at the human beta-globin locus - Fullerton, S; Fullerton, Stephanie (1994)
The investigation of genetic variation at the DMA sequence level in Drosophila has demonstrated the success of the approach for elucidating the impact of molecular, selective, and demographic evolutionary processes. However, sequence level investigation of human genetic variation has thus far been limited to a single locus, the mitochondrial DNA genome. In order to extend the analysis of DNA sequence variation to human nuclear loci, and thereby bring the power of sequence analysis to the investigation of human population origins and affinities, allelic sequence diversity at the human β-globin gene was determined. A 3 kilobase (kb) genomic region, encompassing the human β-globin gene and associated flanking DNA, was examined. DNA sequence variation in this region was identified by direct sequence analysis of alleie-specific PCR amplification products. In total, 173 chromosomes from five human populations from Melanesia, Indonesia, and Africa, were investigated. Thirty-four polymorphisms were identified: 26 silent nucleotide differences, 2 non-silent (β haemoglobinopathies) variants, and 6 small insertion/deletion polymorphisms. These 34 polymorphisms were inherited as 53 different alleles, each defined by a unique sequence haplotype. Only 10 alleles were identified when the same genomic region was investigated by restriction enzyme analysis. The allelic sequence diversity identified suggested much about the influence of molecular, selective, and demographic phenomena. The unexpectedly high level of sequence haplotype polymorphism was found to be consistent with the pronounced impact of interallelic recombination in sequences 5' of the β-globin gene. Despite the presence of selected β haemoglobinopathies in some of the populations investigated, neither the genomic distribution nor the frequency of silent polymorphic sites was found to be inconsistent with that expected of a neutrally-evolving locus. Geographic differences in β-globin diversity were therefore attributed to the effects of mutation in partially subdivided populations as well as in specific cases reduction in population size and gene flow, rather than the influence of natural selection, and evaluated with respect to currently debated hypotheses concerning human evolutionary origins. The investigation of DNA sequence variation at the human β-globin locus has therefore contributed new insights into the evolution of the locus in human populations and provided an important new class of data with which to test hypotheses concerning the genetic origin of Homo sapiens sapiens.